Hagiographic Bandit Slippages: Gaucho Gil in Music and Prose (Periphērica, 2024)
This article examines representations of the Argentine folk saint Gauchito Gil in music and prose as Gil veneration spreads from the Argentine littoral to more urban and para-urban spaces. The movement in space and through genres reflects the play between the hegemonic and the vernacular and the closing of the frontier. First, the article considers Gauchito devotion as a subculture and analyses the production and maintenance of that subculture through chamamés. I argue that Orlando Van Bredam’s novella, El retobado: vida, pasión y muerte del Gauchito Gil, is a textualization of the vernacular devotion practiced by Gil devotees and slips between the novelistic and hagiographic modes. Building from Emilio Willems suggestion that marginal urban neighborhoods constitute an “anonymous frontier,” I then examine the mapping of Gil worship into urban spaces in cumbia villera and stories by Mariana Enríquez. Finally, I address the increasing institutionalization of Gauchito devotion.
Keywords: Gaucho Gil; Vernacular Saints; Banditry; Contemporary Hagiography; Cumbia Villera